Content validity of the WorkHab functional capacity evaluation. (22nd January 2019) - James, Carole; MacKenzie, Lynette; Capra, Mike
Abstract : Introduction: Validity is a dynamic process and as part of a continual process of evaluation of tools, this study aimed to evaluate content validity of the WorkHab functional capacity evaluation, a tool used in occupational rehabilitation. Methods: A cross sectional survey of health professionals who conduct FCEs investigated their ratings of item relevance and item difficulty across different categories of work and injuries. The survey also explored the relationship of the WorkHab FCE items with the physical demand items of the Dictionary of Occupational Titles (DOT). Results: The majority of items of the WorkHab FCE were rated as relevant for manual work and vocational retraining with over 90% agreement between the 106 respondents. Therapists identified the WorkHab items of climbing, crawling and balance as less relevant for sedentary work. Lifting items were perceived as the most difficult for those with a lower back injury, or an upper limb injury. Sixteen of the 18 WorkHab FCE items had 100% agreement with the equivalent items on the DOT. The WorkHab FCE items that had poor agreement with the DOT were mainly sensory items such as see, feel, talk and hear. Conclusions: The findings of this study support the content validity for the WorkHab FCE specifically in relation to manual work and for vocational retraining purposes.